Does the Current British Higher Education System Really Prepare Graduate Animation Students for a Developing and Changing Industry ? - Kennedy-Parr, Sarah Ann (European Scientific Journal, ESJ, 2017)
There is a current trend in UK and Europe for animation students to work on group projects during their studies. ‘Creativity is not purely an individual performance. It arises out of our interaction with ideas and achievements of other people. It is a cultural process.’ (Pg 12. Robinson). Gobelins in Paris, was one of the first animation schools to start this trend and the final films were slick and professional with an incredibly long list of credits. Many of the graduates went straight into industry working as technical operators, animation assistants or riggers and many UK animation schools soon followed suit supported by institutions like Skillset (a UK government body set up to link industry with education). The idea has been championed by industry and a trend has started for animation courses to apply for Skillset or other similar accreditation bodies to give their courses a stamp of approval. These accreditation bodies have a say in how the course curriculum is taught and if the courses don’t follow their advice, there is a danger that this stamp of approval will be removed. The question is, does this turn out interesting creatives or factory style technicians specialising in one skill to fit into a large team of people. Robinson also goes on to say, ‘Creativity requires an atmosphere where risk taking and experimentation are encouraged rather than stifled’ (Pg 12. Robinson) . Is this ‘group work training’ a short sighted solution for today’s industry creatives and directors to solve an immediate skills shortage or will this stratégy keep the British animation industry at the cutting edge of creativity and innovation on the worldside stage?